INFLUENCE OF INDIVIDUALIZED EARLY REHABILITATION ON INFLAMMATION, ENDOTHELIAL DYSFUNCTION, AND PULMONARY HEMODYNAMIC PARAMETERS IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - A.Kh Abdullaev; J.O. Matkomilov (Journal of modern medicine, 2026)
This study evaluated the effect of an early comprehensive rehabilitation program—comprising physical therapy (exercise therapy), a herbal preparation, and magnetotherapy in addition to standard treatment and standard rehabilitation—on inflammation, endothelial dysfunction, and pulmonary hemodynamics in 127 patients with chronic obstructive pulmonary disease (COPD). The results demonstrated that in the main group, the levels of TNF-α decreased significantly by 43.91–51.58%, VEGF by 49.50–50.46%, and Endothelin-1 by 46.03–47.27% (p<0.001). In addition, echocardiographic evaluation revealed a marked reduction in systolic pulmonary artery pressure (SPAP). These findings confirm the high clinical and pathogenetic efficacy of early comprehensive rehabilitation in reducing chronic inflammation, correcting endothelial dysfunction, and improving pulmonary hemodynamics in COPD patients.